Praktik Budaya Literasi Dalam Peningkatan Kompetensi Literasi Di Madrasah Tsanawiyah Al-Muhajirin Purwakarta - Saepul Malik, Amit (LPTK UIN Syekh Wasil Kediri, 2024)
This research uses descriptive research methods with a qualitative approach. The data collection techniques used were observation, interviews and documentation. Primary data was obtained from interviews with residents of Al-Muhajirin Purwakarta Madrasa Tsanawiyah (MTs) school. Secondary data comes from archives, reports and documents related to research. Literacy activities held at MTs Al-Muhajirin include the Al-Muhajirin Literacy Movement, Language Performance or Confident Show, language competition, poetry writing competition where the books will later be recorded as an anthology of student poetry, and a short story writing competition. The literacy culture practices held at MTs Al-Muhajirin have been carried out systematically and intensively, so that they can produce children and teachers who excel in writing, and from these agendas MTs Al-Muhajirin has produced books by children, teachers and heads of madrasa.